1997
DOI: 10.1086/310819
|View full text |Cite
|
Sign up to set email alerts
|

Observations and Theoretical Implications of GRB 970228

Abstract: GRB 970228 is the first gamma ray burst for which prolonged post-burst transient x-ray, optical, and infrared emission has been detected. Recent Hubble Space Telescope observations show that the transient consists of two components: a point source, which is known to be fading, and an extended source, which is possibly fading. I fit standard fireball remnant models to the first month of x-ray, optical, and infrared measurements, which may be done without assuming a GRB distance scale. I show that its emission i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
29
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 14 publications
(20 reference statements)
8
29
1
Order By: Relevance
“…A strong confirmation of the generic fireball shock model came from the correct prediction [43], in advance of the observations, of the quantitative nature of afterglows at longer wavelengths, in substantial agreement with the subsequent data [89,85,91,73,96]. The measured 7-ray fluences imply a total energy of order 10 54 (^7/47r) ergs, where Af2 7 is the solid angle into which the gamma-rays are beamed.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…A strong confirmation of the generic fireball shock model came from the correct prediction [43], in advance of the observations, of the quantitative nature of afterglows at longer wavelengths, in substantial agreement with the subsequent data [89,85,91,73,96]. The measured 7-ray fluences imply a total energy of order 10 54 (^7/47r) ergs, where Af2 7 is the solid angle into which the gamma-rays are beamed.…”
Section: Introductionsupporting
confidence: 74%
“…However in early 1997 the Italian-Dutch satellite Beppo-SAX suceeded in providing accurate X-ray locations and images that allowed their follow-up with large ground-based optical and radio telescopes. The current interpretation of the gamma-ray and longer wavelength radiation is that the progenitor trigger produces an expanding relativistic fireball which can undergo both internal shocks leading to gamma-rays, and (as it decelerates on the external medium) an external blast wave and a reverse shock producing a broad-band spectrum lasting much longer.A strong confirmation of the generic fireball shock model came from the correct prediction [43], in advance of the observations, of the quantitative nature of afterglows at longer wavelengths, in substantial agreement with the subsequent data [89,85,91,73,96]. The measured 7-ray fluences imply a total energy of order 10 54 (^7/47r) ergs, where Af2 7 is the solid angle into which the gamma-rays are beamed.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…While the former question is still far from being settled, the multi-wavelength observations (e.g., Frail et al 1997;Metzger et al 1997;Reichart 1997;Waxman 1997; see also Piran 1999 for a review), which become available in the past few years, give strong support to the fireball shock model (Rees & Mészáros 1992, 1994. In its most general form, this model considers GRB emission as the result of energy dissipation in relativistic shock waves and assumes that all the energy is initially accumulated in the form of ultrarelativistic outflow (fireball) with a Lorentz factor Γ greater than 100 (Baring & Harding 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The first transient optical counterpart, of GRB 970228, is in a faint galaxy with 0 8 ¼¼ diameter (Sahu et al 1997). Several authors (Wijers, Rees, & Mészáros 1997;Reichart 1997;Waxman 1997a) showed that to first order this model describes the X-ray and optical afterglow of GRB 970228 very well. The detection of absorption features in the OT's spectrum of GRB 970508 (Metzger et al 1997) established that this event was at a redshift greater than z 0 835.…”
Section: L28mentioning
confidence: 99%